"Not just a hobby, but a lifestyle": Characteristics, preferences and self-perception of individuals with different levels of involvement in birdwatching. - Emilia Janeczko (Public Library of Science (PLoS), 2021)
Birdwatching is one of the most sustainable types of nature-based tourism and, at the same time, a form of recreation that is developing very dynamically. Birdwatching is attracting more and more people, not only professionals, but also amateurs from many countries. Birdwatching research is still relatively embryonic, especially when compared to nature tourism or wildlife tourism. Our main aim was to determine preferences and opinions of birdwatchers visiting the largest national park in Poland, in relation to their different levels of involvement. The data were collected in 2018 from a survey of a sample of 357 Polish and foreign birdwatchers. Results showed that birdwatcher respondents were predominantly male, middle-aged, and living in a large city. An important tool described in this article is a new scale that assesses the level of involvement of individual people engaged in birdwatching activity. This scale corresponds well with the individual characteristics of birdwatchers. Most birdwatchers defined their birdwatching activity as a permanent rather than a temporary hobby and therefore considered it to be more of a lifestyle than a hobby. Engagement in birdwatching activity increased with age and frequency of trips. The two most important reasons for birding were 'to be close to nature' and 'fascination with birds'. It has been proven that the development of birdwatching in the future will require a developed infrastructure enabling interaction with the objects of observation.